THE HISTORIC CENTRE OF LIMA, PERU: NEW USES OF JIRON DE LA UNION STREET - Gregório de Andrade, Rita de Cássia; Morais Soares, Maria Simone (GeoTextos, 2013)
The city of Lima was founded in 1538. It currently has a population of about 8.486.866 and presents several complex problems of space organization, so that specific studies are needed to understand its reality. The Historical Center of Lima is locus of patrimonial management policies since the eighties. In this context, the Jirón de la Unión Street, the main of this urban space, deserves to be analyzed. The principal aim of this study is to analyze the new uses of Jirón De La Unión Street, in the historical center of Lima. The methodological procedures used to carry out this research were: bibliographical, cartographic, photographic and documentation surveys, together with outdoor researches to characterize the use of the soil and related landscape. A first observation was the predominant commercial use of the current Jirón de la Unión Street.